A flat-panel-shaped hybrid piezo/triboelectric nanogenerator for ambient energy harvesting. (4th April 2017) - Hassan, Gul; Khan, Fasihullah; Hassan, Arshad; Ali, Shawkat; Bae, Jinho; Lee, Chong Hyun
Abstract: Recently, many researchers have been paying attention to nanogenerators (NGs) as energy sources for self-powered mirco-nano systems, and studying how to achieve their higher power generation. Hence, we propose a hybrid-type NG for harvesting both the piezoelectric and triboelectric effect simultaneously. In the proposed hybrid NG, the piezoelectric NG (PNG) and triboelectric NG (TENG) are fabricated using polydimethylsiloxane (PDMS) and perovskite zinc stannite (ZnSnO3 ) nanocubes with a high charge polarization of 59 uC cm −2 composite (PDMS + ZnSnO3 ) and UV surface-treated PDMS, respectively. To effectively combine a high output current of PNG and a high voltage of TENG, these two NGs are stacked upon each other, and separated by sponge spacers providing a uniform air gap for the triboelectric effect. In particular, this fabricated structure has a low Young's modulus for piezoelectricity. The proposed hybrid NG device effectively achieves a combined peak voltage of 300 V on an open circuit, a power density of 10.41 mW cm −2 at 1 MΩ load, and a maximum short circuit current density of 16 mA cm −2 at 50 Ω load. It is feasible that the proposed NG can be utilized as a source for various self-powered systems.